Determinants of intention to disclose musculoskeletal injury in adolescent athletes - Cheever, K. M.; Dewig, D.; Nedimyer, A. K.; Register-Mihalik, J. K.; Kossman, M. K. (Journal of Athletic Training, 2024)
Key Points